АНТРОПОЦЕНТРИЧЕСКИЕ ПРОВЕРБИАЛЬНЫЕ ОБРАЗОВАНИЯ С ОЦЕНКОЙ ВНЕШНОСТИ И ВОЗРАСТА ЧЕЛОВЕКА - Жалгасов, Н.М. (SCIENCE and SOCIETY, 2023)
The present article is devoted to the investigation of the specifics describing the appearance and the age of a person, reflected in semantics of English, Uzbek and Karakalpak proverbs. The author compares the proverbs of three languages and outlines their ethnic-specific features and finds corresponding equivalents / analogues (in cases when it is possible). Theoretical content of the article is approved by examples of the proverbs of compared languages.